Human health risk associated with nitrates in some vegetables: A case study in Gonabad - Mehdi Qasemi; Mansoureh Ghorbani; Rezvan Salehi; Syyed Mahmood Attari; Mojtaba Afsharnia; Mohammad Hadi Dehghani; Mansoureh Farhang; Asma Zarei; Akram Gholinejad; Ahmad Zarei (Food Chemistry Advances, 2024)
Vegetables are vital parts of the human diet, however, they also may contain substances such as nitrate which can affect human health. This cross-sectional research was conducted with the objective to assess the health risk of citizens in Gonabad from nitrate exposure through the consumption of some vegetables. Common vegetables namely, cucumber, carrot, tomato, potato, lettuce, cauliflower, onion and mushroom were analyzed for nitrate contents. The values of the estimated daily intakes (EDIs), target hazard quotients (HQs) were computed to estimate the non-carcinogenic health risk. Nitrate concentrations in the selected vegetables ranged from 25 to 2100 mg/kg (fresh weight). The highest concentration of nitrate was found in lettuce (2100 mg/kg). The EDI values in some vegetables exceeded the acceptable daily intake of nitrate. The calculated HQ values of carrot, potato, lettuce, onion and mushroom were HQ ≥ 1 for children, signifying non-carcinogenic health risk to the age group. For teenagers group, the HQ values for lettuce and onion was ≥ 1. Furthermore, potato, lettuce and onion were unsafe considering HQ values related to nitrate concentration in adults. Therefore, the control of possible contamination sources and minimization of vegetable nitrate concentration are recommended.